Comparative analysis of surgical outcome of treatment of supracondylar humerus fractures Gartland’s extension type III by using closed reduction and K –wire fixation versus open reduction and K –wire fixation method - Keche, Nilesh Janardan; Kale, Abhijit Bhimrao; Sheth, Binoti Arun; Rathod, Ashok Kumar (International Journal of Research in Orthopaedics, 2017)
Background: Supracondylar fractures of the humerus are the most common elbow fracture in children of the age group 4-12 years. The modern approach for its treatment includes closed reduction or open reduction and internal fixation with K wires. The aim of the present study was to evaluate the clinical and radiological results of children who were treated with the two surgical approaches. Methods: In our institute children who underwent surgical treatment for supracondylar humeral fractures by closed reduction or open reduction and internal fixation with K wires and whose data were available with regular follow-up of at least 1 year were included in the study. Each group included 25 children in each. Clinical and radiological outcomes were evaluated and compared among the study groups. Results: The mean age of the patients in both the groups were 6.84 and 6.64 in group 1 and group 2 respectively. Fractures were more in boys compared to girls in both the groups. Most of the fractures were seen on left side with posteromedial displacement of distal fragment in almost 80% in both the groups. Mean change in Baumann’s angle (BA), carrying angle and range of motion (ROM) as compared to normal side in both the groups after 3rd and 9th month of follow ups was found to be not statistically significant. Overall result according to Flynn’s criteria was 60% excellent in group 1 as compared to 52% in group 2. Mean satisfaction score was also more in group 1 children when compared to group 2. Conclusions: Closed reduction with internal fixation with K wires was found to be a better choice of treatment with good functional results.